Flexible Fringe Effect Capacitive Sensors with Simultaneous High‐Performance Contact and Non‐Contact Sensing Capabilities. Issue 2 (2nd November 2020) - Ruth, Sara Rachel Arussy; Feig, Vivian Rachel; Kim, Min-gu; Khan, Yasser; Phong, Jason Khoi; Bao, Zhenan
Abstract : To mimic human touch sensing, robotics must be able to leverage multiple sensory inputs. Previously, to achieve both proximity and pressure sensing, most approaches have required using two separate sensors, each with their corresponding electronics, limiting the achievable density. More recently, sensors with multifunctional pressure and proximity capabilities have been realized at the cost of compromised pressure sensing. Presented here is a new design for a multifunctional interdigitated fringe field capacitive pressure sensor with a pyramid microstructured dielectric layer that has proximity‐sensing capabilities (noncontact mode) while also sensing pressure (contact mode) as strongly as an equivalent parallel plate capacitive sensor of the same size. In contact mode, both sensors have a response time of less than 20 ms and can respond to loads lighter than 0.5 Pa. Further, the interdigitated fringe field sensor can clearly distinguish between the two sensing modes, as well as between conductive and nonconductive materials in the noncontact mode. Finally, we use the interdigitated fringe field sensor to demonstrate both proximity and high‐sensitivity pressure sensing on a robotic gripper. Abstract : Multifunctional sensors are integral for high‐density sensing matrices to mimic human touch. To achieve this, a novel interdigitated fringe field sensor with pyramid microstructures enables proximity sensing without compromising on the pressure‐sensing performance. The sensor's pressure‐sensing performance is similar to an equivalent high‐sensitivity parallel plate capacitive pressure sensor and has the capability to distinguish between contact and noncontact sensing.